Immunohistochemical evaluation of leiomyoma tissue and normal myometrium in patients with uterine leiomyoma during hypo- and hyperestrogenic conditions caused by of use of gonadotropin-releasing hormone analogues. - Medvedev, M. V. (Морфологія / Morphologia / Morfologìâ, 2012)
In study immunohistochemical analysis of markers of proliferation, apoptosis, extracellular matrix degradation, angiogenesis and steroid hormone receptors in myomatous tissue and myometrium was conducted in 62 patients with uterine leiomyomas during long-term and short-term correction of hormonal status by gosereline acetate.Studies have shown that pseudocapsule of fibroids at immunohistochemical level is unchanged myometrium.For leiomyoma tissue compared to myometrium were characteristic greater expression of steroid hormone receptors and aromatase, inhibition of apoptosis, greater expression of angiogenic factors compared to unchanged myometrium.Under the action of GnRH-a direct and mediated by reduction of estradiol occurred molecular changes, which cover almost all parts of the pathogenesis of fibroids and include inhibition of expression of estrogen receptor and aromatase synthesis, enhancing of expression of progesterone receptors, inhibition of proliferation and angiogenesis, accelerated degradation of ECM. Under the influence of hyperestrogeny caused by flare-up effect of GnRH-a and direct peripheral effect of GnRH analogs progression of uterine leiomyoma provides increased sensitivity of uterine myocytes to ischemia.Despite the obvious role of antiapoptotic factor bcl-2 in the pathogenesis of uterine fibroids, short-and long-term hormonal treatment with GnRH-a does not lead to significant changes in its expression.